TECHNOLOGY OF BIOETHANOL PRODUCTION FROM RENEWABLE RAW MATERIALS (Scientific journal of the Fergana State University, 2024)
The main objective of this study is to propose a methodology for evaluating alternatives for the synthesis of the second-generation bioethanol production process from lignocellulose raw materials in order to reduce waste, energy consumption and production costs. The methodology is based on modeling, synthesis, design and simulation, where the integration of heat into the 2P bioethanol production process is a key tool for evaluating the process from a technical, economic and environmental point of view. As an example, we can cite ordinary cane, which is considered as a raw material, and modeling is performed using a modular process simulator. To evaluate and compare alternatives to bio-purification, the selected evaluation criteria are ethanol yield, unit cost, energy consumption, CO2 emissions and water consumption. The results show the best technological alternatives that can lead to more sustainable ethanol production, contributing to more efficient decisions in the synthesis and design of bio-treatment facilities.